Presencia de agentes patógenos presentes en leche de vaca con mastitis subclínica en la Parroquia Pimocha Cantón Babahoyo - Molina Moreno, Angie Michell (2024)
Mastitis is considered an infectious disease, caused by more than 100 microorganisms, mainly staphylococci, streptococci and gram-negative bacteria. The type of research applied is evaluative and descriptive, where the results obtained on the incidence of pathogenic agents present in milk from cows with subclinical mastitis in the Pimocha Parish, Babahoyo Canton, were evaluated. In the Pimocha Parish, cows were sampled in production stages in which the 336 mammary quarters corresponding to 84 animals analyzed by CMT in the three dairy herds were evaluated, 54 cows were positive for subclinical mastitis, representing (64.28%), 9 cows were positive for clinical mastitis representing (10.71 %) and 21 cows with negative cases representing (25%). Using the microbiological culture technique on the farms under study in which the main predominant microorganisms were: Streptococcus uberis, Staphylococcus spp., Streptococcus dysgalactiae.